Performance Evaluation of U-Turn Bridge Deck Rehabilitation: A Case Study on Highway No. 35 Thailand - Meepunyo, Kittamet; Yodsudjai, Wanchai; Yindeesuk, Sukit (Srinakharinwirot University Engineering Journal, 2025)
This research aims to evaluate the structural performance of a U-turn bridge by analyzing its deflection behavior and internal forces both before and during the rehabilitation process, in order to assess structural stability and safety throughout the construction phase. The study focuses on comparing two rehabilitation approaches: one without steel girder reinforcement and the other with steel girder reinforcement, to examine the impacts of each method. The results indicate that rehabilitation without girder reinforcement led to an average deflection increase of 188.2% compared to the pre-rehabilitation condition. In contrast, the use of steel girders reduced the average deflection by 67.3% compared to the non-reinforced method. These findings clearly demonstrate that steel girder reinforcement significantly enhances the safety and stability of the structure during rehabilitation. In practical applications, the results of this study can be utilized to support the planning, development, or improvement of U-turn bridge rehabilitation strategies, with an emphasis on techniques that enhance efficiency and safety during execution.